OXavidin for Tissue Targeting Biotinylated Therapeutics. (10th January 2010) - De Santis, Rita; Albertoni, Claudio; Rosi, Antonio; Leoni, Barbara; Petronzelli, Fiorella; D'Alessio, Valeria; Nucera, Eleonora; Salvatori, Giovanni; Paganelli, Giovanni; Verdoliva, Antonio; Carminati, Paolo; Nuzzolo, Carlo Antonio
Abstract : Avidin is a glycoprotein from hen egg white that binds biotin with very high affinity. Here we describe OXavidin, a product containing aldehyde groups, obtained by ligand-assisted sugar oxidation of avidin by sodium periodate. OXavidin chemically reacts with cellular and tissue proteins through Schiff's base formation thus residing in tissues for weeks while preserving the biotin binding capacity. The long tissue residence of OXavidin as well as that of OXavidin/biotinylated agent complex occurs in normal and neoplastic tissues and immunohistochemistry shows a strong and homogenous stromal localization. Once localized in tissue/tumor, OXavidin becomes an "artificial receptor" for intravenous injected biotin allowing tumor targeting with biotinylated therapeutics like radioisotopes or toxins. Moreover, present data also suggest that OXavidin might be useful for the homing of biotinylated cells. Overall, OXavidin exhibits a remarkable potential for many different therapeutic applications.